Analysis of Hypertension Risk Behavior - Siregar, Siti Maisyaroh Fitri; Lubis, Adelina Irmayani (Universitas Teuku Umar, 2022)
Hypertension is not only experienced in old age but in the last decade shows data on hypertension experienced by adults and even adolescents. The risk factors for hypertension do not result in the incidence of hypertension in a fast period, but a long/latent, so adolescents who behave at risk of hypertension are feared to contribute to increasing the incidence of hypertension in the young adult and old adult age groups. The purpose of this study is to identify and analyze risky behaviors in adolescents. The method used in this study is a quantitative design with a cross-sectional design. The sample of this study was late adolescence.The results showed that adolescents who consumed salt more than 1 tablespoon per day 81.2%, often smoked 80.1%, ate fatty 59.2%, never physical activity 70.2%, never consumed vegetables 48.9%, consumed junkfood 80.1%, and had a history of hypertension 33.3%. Conclusion of 7 variables as risky behavior 3 measurable variables are often carried out by adolescents, namely smoking, not doing physical activity, and never consuming vegetables. Health promotion of hypertension prevention needs to be instilled early so that adolescents behavior has good hypertension prevention behavior